DuraTable Enterprises Inc. - Spencer D. Evans; Hal B. Heaton (The Journal of Entrepreneurial Finance (JEF), 2018)
In late 2017, DuraTable received a number of unsolicited inquiries regarding its interest in selling out in a going private transaction, mostly from private equity firms. Since the chairman of the board and founder, Gary Reynolds, was approaching retirement age and the largest single shareholder who had provided the seed capital to start the company was over 80 years old, Mr. Reynolds was willing to consider a sale and provided information to four or five of them to prepare bids. DuraTable was a closely held company with relatively few individuals holding the vast majority of shares. As such, DuraTable's shares traded infrequently. As a result, Mr. Reynolds questioned if even the share price itself appropriately reflected the value of the company. As he looked forward to a meeting that would be held with Pierce the following week, Mr. Reynolds asked himself, 'What price would reflect a fair valuation of DuraTable's operations?'.
Keywords: G32; G34; 650; acquisition; private equity; small business; entrepreneurship; valuation